The Political Economy of Upgrading Regimes: Brazil and beyond - Schedelik, Michael. author. aut Link
XXIII, 286 p. 48 illus., 1 illus. in color.
Keywords: In his wonderfully researched and tightly argued book, Michael Schedelik explains why the Brazilian development strategy of significantly raising the level of technological development in order to be less dependent on raw material exports was not successful. A must-read for students of innovation processes in emerging economies for many years to come. Andreas Nölke, Professor of Political Science, Goethe University Frankfurt Innovation in Brazil has been a topic of extensive research, but rarely before Michael Schedelik’s book has it been done as comprehensively with such a wealth of empirical evidence. Ben Ross Schneider, Ford International Professor of Political Science and Director of the MIT-Brazil Program, Massachusetts Institute of Technology This is a path breaking contribution to the study of comparative political economy of development in emerging economies. It is a provocative must read for those who strive to avoid simplistic structural and facile political explanations of upgrading development. Antonio José Junqueira Botelho, Professor of Comparative Political Economy, IUPERJ Universidade Candido Mendes, Rio de Janeiro Today’s middle-income countries tend to be locked in a middle-income trap, unable to transition to higher income levels due to rising costs and declining competitiveness. While there is a broad consensus that upgrading these economies towards innovation-led growth is imperative, countless institutional and political economy obstacles remain. This book brings together analytical perspectives from comparative political economy, innovation studies, and development economics for the study of technological upgrading. Its distinctive contribution is the development of an innovative theoretical framework, named upgrading regimes, combining and extending the comparative capitalism and innovation system perspectives. It explores the usefulness of this approach by providing an indepth assessment of the political economy of upgrading in Brazil under the Workers’ Party governments. As the politics of technological upgrading will be one of the crucial research areas in the years to come, this book promises to become a key reference point in this debate. Michael Schedelik is Lecturer and Research Associate at the Institute of Political Science at Goethe University Frankfurt. His research focuses on the politics of growth and innovation in developing and emerging economies.